INTERRUPTION OF THE RUNNING OF THE LIMITATION PERIOD BY PERFORMING ACTIONS EVIDENCING THE ACKNOWLEDGEMENT OF THE DEBT - Gabuzyan, Kristine (State and Law, 2022)
The current article discusses the issue of interrupting the limitation period by performing actions that confirm the acknowledgement of the debt. The article discusses the main criteria that an action must meet in order to be considered an acknowledgment of debt and the absence of which carries great risks of practical problems. From this point of view, the importance of the certainty and clarity of the recognition of the debt, in particular, of its nature and content, as well as the expression of the will to fulfill the obligation in the future is noted. In addition, in order to simplify civil circulation, as well as to ensure the protection of the debtor’s expectations, it is proposed to introduce regulation, which allows to restart the running of the limitation period by the acknowledgement of the debt even after the expiration of the limitation period.